An approach to the comparison of parallel program scalability - Teplov, A.M. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2014)
An approach to the scalability analysis of parallel programs is proposed. The introduced definition of scalability allows one to take into account the effect of startup parameters on the program execution quality. A concept of the scalability metric and scalability mark for parallel programs is also introduced. An approach to the comparison of parallel program scalability based on the use of the scalability mark as a part of the parallel program scalability metric is described. Some comparative results of scalability study using this approach are discussed by several examples of parallel programs.